THE EFFECTIVENESS OF POP-UP BOOK IN IMPROVING STUDENTS’ READING INTEREST - Muh. Yusuf, Andi; Jusriati; Sari, Puspa (Universitas Cokroaminoto Palopo, 2023)
The effectiveness of pop-up books in increasing students' reading interest at SMPN 3 Palopo, reading interest is the sole focus of this research. In this study, narrative text is the lesson the researcher is trying to convey. Researchers used a total sampling sample consisting of 31 students. The instruments in this study were questionnaires and observation checklists. Researchers collected data through questionnaires. Data were statistically analyzed using SPSS edition 25. The researcher concluded that the use of Pop-up books increased students' interest in reading at SMPN 3 Palopo. This is evidenced by the results of the post-test (39.6) which are higher than the pre-test (28.2). Also, the t-count score (-19.183) is higher than the t-table (2.042). This shows that by using pop-up book media students' interest in reading increases.